2015
DOI: 10.18632/oncotarget.5153
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in the TERT and CLPTM1L gene region and gastrointestinal stromal tumors risk

Abstract: Recent studies have suggested polymorphisms in the TERT and CLPTM1L region are associated with carcinogenesis of many distinct cancer types, including gastrointestinal cancers. However, the contribution of polymorphisms in the TERT and CLPTM1L gene region to gastrointestinal stromal tumors (GISTs) risk is still unknown. We tested the six tagSNPs on TERT and CLPTM1L region with GIST risk, using a population-based, two-stage, case-control study in 2,000 subjects. Functional validation was conducted to validate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…In 2015, Zhang et al found that the C allele of rs2736098 was associated with an increased risk of gastrointestinal stromal tumor. 42 However, in the current study, rs2736098 exhibited no association with NSCLC in a Chinese Han population, and this finding is consistent with those of a study of hepatocellular carcinomas by Yuan et al 43 Moreover, the results related to rs2853676, 44 , 45 rs10069690, 46 , 47 rs2075786, 48 , 49 and rs2736122 21 , 50 have exhibited inconsistencies in different studies (including the current study). The reasons for these inconsistencies could be related to the different diseases studied and different genetic backgrounds of the studied populations.…”
Section: Discussionsupporting
confidence: 89%
“…In 2015, Zhang et al found that the C allele of rs2736098 was associated with an increased risk of gastrointestinal stromal tumor. 42 However, in the current study, rs2736098 exhibited no association with NSCLC in a Chinese Han population, and this finding is consistent with those of a study of hepatocellular carcinomas by Yuan et al 43 Moreover, the results related to rs2853676, 44 , 45 rs10069690, 46 , 47 rs2075786, 48 , 49 and rs2736122 21 , 50 have exhibited inconsistencies in different studies (including the current study). The reasons for these inconsistencies could be related to the different diseases studied and different genetic backgrounds of the studied populations.…”
Section: Discussionsupporting
confidence: 89%
“…The 45 studies included nine on breast cancer (Garcia‐Closas et al, ; Haiman et al, ; Huo et al, ; Michailidou et al, , ; Palmer et al, ; Purrington et al, ) and, six on ovarian cancer (Bojesen et al, ; Earp et al, ; Kuchenbaecker et al, ; Lee et al, ; Phelan et al, ; Terry et al, ); five on lung cancer (Gao et al, ; Landi et al, ; Wang et al, ; Ye et al, ; Zhao et al, ). two each on glioma (Melin et al, ; Zhao et al, ), thyroid cancer (Gong et al, ; Gudmundsson et al, ), pancreatic cancer (Campa, Rizzato, et al, ; Petersen et al, ), prostate cancer (Panagiotou et al, ; Schumacher et al, ), colorectal cancer (Li et al, ; Pellatt, Wolff, Herrick, Lundgreen, & Slattery, ), RCC (Martino et al, ; Wu, Yan, et al, ), and leukemia (Sheng et al, ; Speedy et al, ); and one each on endometrial cancer (Prescott, McGrath, Lee, Buring, & De Vivo, ), bladder cancer (Rothman et al, ), testicular germ cell tumor (TGCTs) (Schumacher et al, ), melanoma (Llorca‐Cardenosa et al, ), multiple myeloma (Campa, Martino, et al, ), gastrointestinal stromal tumors (GISTs) (Zhang et al, ), non‐Hodgkin's lymphoma (NHL), diffuse Large B‐cell lymphoma (DLBCL), small lymphocytic lymphoma/chronic lymphocytic leukemia (SLL/CLL) (Shadrina et al, ), nasopharyngeal carcinoma (NPC) (Zhang et al, ), gastric cancer (Duan et al, ), esophageal cancer (Wu, Yan, et al, ), gastric cardia adenocarcinoma (GCA) (Zhang et al, ), hepatocellular carcinoma (HCC) (Zhang et al, ). One study focused on Caucasians (Prescott et al, ); two studies focused on Africans (Huo et al, ; Long et al, ); three studies on African‐Americans (Bojesen et al, ; Haiman et al, ; Palmer et al, ), 16 studies on Asians (Bojesen et al, ; Duan et al, ; Gao et al,…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly we found that SORE6+ cells have increased expression of two genes known to enhance resistance to drugs by different mechanisms. CLPTM1L, also known as cisplatin resistance-related protein 9, confers resistance to apoptosis caused by genotoxic agents and leads to up-regulation of the anti-apoptotic protein, Bcl-xL [66,67]. CYP3A5 encodes a member of the cytochrome P450 superfamily of enzymes, which have multiple functions in drug metabolism and in facilitating the elimination of drugs [68].…”
Section: Discussionmentioning
confidence: 99%